THE EFFECT OF MONEY AVAILABILITY FOR SHOPPING ON IMPULSIVE PURCHASING IN DIFFERENT CULTURES: THE MODERATING EFFECT OF INFLUENCE OF SHOPPING COMPANION - Dinesha, P (PEOPLE: International Journal of Social Sciences, 2017)
The paper investigates the relationship between the availability of money for shopping activities and impulsive purchasing of consumers. Further, it is observed whether decisions of consumers are changed when they go shopping with someone which means the moderating effect of influence of shopping companion on impulsive decisions of the consumers. The study will be really significant as it examines the influence of other persons in buying decisions whereas most of previous studies come out with individual level factors. For the study a sample was conveniently selected consisting 150 respondents representing Norway and Sri Lanka. The survey was employed as the tool to collect primary data by using self-administered questionnaire. Through the findings it was revealed that, the availability of money shows significant positive relationship in consumers’ impulsive purchasing of both nationalities. However, as further results shopping companions significantly influence the relationship between main variables: availability of money and impulsive buying but that is only related to Sri Lankan Sample. The future research implications have discussed.